PENGARUH PIJAT BAYI DAN PERMEN GUMMY GUNA MEWUJUDKAN DESA BEBAS STUNTING - Fitrianingtyas, Rizki; Mauludiyah, Zaida; Hidayati, Sholihatil; Mayasari, Shinta (Proceedings of Annual Conference on Community Engagement, 2023)
Malnutrition in children is still a crucial public health problem and remains a burden globally, especially in developing countries. Childhood malnutrition is directly linked to childhood cognitive development and physical growth and has emerged as one of the strongest single risk factors for early neonatal mortality and morbidity. The effects of malnutrition include frequently experiencing various infections including diarrhea, pneumonia and malaria, and around 45% of deaths of children under 5 years are caused by factors related to nutrition. Stunting in Indonesia is still a major health problem. Jember Regency has the highest STUNTING rate number 1 in East Java. The importance of the stunting problem requires many parties to make efforts to reduce the incidence of stunting in developing countries, including Indonesia. The role of public health workers as promoters in promoting health is very important in efforts to provide education to the public about efforts to increase children’s nutritional intake by processing food and preventing stunting through baby massage. One program that can be a driving factor is the empowerment of women, especially mothers, who play an important role in the family. This activity aims to overcome stunting by increasing toddlers’ appetite with baby massage, increasing knowledge about the use of protein-based functional food for toddlers into candy through empowering women in the community.